Peritoneoscopic implantation of Tenckhoff catheter and indications for laparoscopy in children with long-term abdominal peritoneal dialysis - Zachariou, Zacharias; Daschner, Markus; Waag, Karl-Ludwig (Pediatric endosurgery & innovative techniques, 2000)
Tenckhoff catheters (TC) are inserted usually by laparotomy in children with terminal renal insufficiency. Catheter malfunction is the most common reason for interruption of therapy. Over 18 months, the authors performed 13 peritoneoscopic TC implantations in children between 1 and 9 years of age. In 9 cases, the TC was placed primarily, and no complications occurred over a follow-up period of 8-18 months. In 4 cases, the TC was implanted secondarily to previous open surgical implantation after removal 1 week earlier. Good function was achieved in 2 cases; in the other 2, function was impeded, so that new catheters had to be implanted via laparotomy. Since 1996 the authors have implanted 73 TC by the open surgical approach. In 12 cases, laparoscopy was performed because of catheter malfunction. In 9 cases, dialysis could be reestablished, as cysts could be removed or the dislocated pigtail could be placed correctly. In the other 3 cases, TC function could not be reestablished by laparoscopic means, and laparotomy was necessary. In primarily peritoneoscopically placed TCs, the pneuperitoneum was set by Veress needle. A needlescope (2 mm) and one forceps (1.7 mm) were used if needed. In the secondarily placed TCs, a 4-mm laparoscope was used. The abdomen was dissected at the implantation site (1.5 cm), and the rectus fascia was opened (1 cm). The muscle fibers were dissected, and the peritoneum was punctured with a split cannula (3.5 mm) under laparoscopic control. The catheter was passed through, and the cannula was removed after splitting. The cuff was placed under the fascia, which was then sutured. The TC was passed through the subcutaneous channel. The results on this limited patient group suggest that laparoscopy is a viable method for controlling catheter malfunction, and peritoneoscopic placement of TCs could be the technique of choice in the future.